SIDALUT Prototype Application for Patient Dental and Oral Health Care - Erwin, Erwin; Emini, Emini; Widiyastuti, Rini (Center of Excellent (Pusat Unggulan Iptek), 2024)
Background Dental and oral therapists are required to carry out dental and oral health care services. The results of the researcher's observations showed that there were still obstacles in the health service to implement a good care process. Problems include not understanding or forgetting how to write a diagnosis statement according to the concept of dental hygienist darby & walsh, not having a dental hygienist darby & walsh textbook as a guideline, and it is impractical to use the textbook because of the thick pages of the book and in a foreign language. Therefore, a more effective and efficient tool is needed as a reference / guideline by students and TGM at the health center, one of which is in the form of a web application prototype. in this study the researcher intends to develop a dental and oral health care application which is the main task of dental and oral therapists. The initial focus of the case is for pediatric patient services at the health center. The purpose of this study is to determine the prototype form of a web-based oral health care application as a guideline for pediatric patient services at the health center. This type of research method is research and development (R & D). Initial research was carried out with descriptive qualitative. The stages of the activity are preparing the material database, making web-based applications with the help of the IT team, then reviewing the material by experts. The results of the research Prototype of oral health care applications can be accessed online based on a website both through laptops, PC, tablets and handphone. The application contains patient data menu features, assessment, diagnosis, planning, implementation, evaluation, and documentation (printing). Expert review shows the majority of answers strongly agree and agree to 9 indicators of material suitability Conclusion A prototype of oral health care application for pediatric cases at the health center has been created under the name SIDALUT (oral health care documentation system).